Quality Control Barriers in Adapting ’Metro-Centric’ Education to Regional Needs - Nagy, Judy; Robinson, Susan R. (Australian and International Journal of Rural Education, 2013)
The massification and globalization of higher education, combined with the widespread adoption of processes underpinning accreditation and quality control of university programs, have tended to result in learning contexts that are increasingly narrowly conceived and tightly controlled. Underlying many quality control measures is a ’one size fits all’ presumption that all qualifying students will receive the same standardized package of resources, teaching, assessment and learning opportunities in each location where a program is offered. This ‘metro-centric’ view gives little regard to the challenges faced by regionally-based institutions and remote campuses in striving to achieve student learning outcomes that are comparable with city-based experiences. Metro-centrically imposed standards for the student learning experience ignore greater delivery costs faced by regional campuses due to thin markets and diseconomies of scale, plus higher costs for regional construction and for ongoing supply of information technology. In addition to these economic constraints, procedural inflexibilities within ‘mother’ campuses linked to quality control procedures, combined with accreditation requirements imposed by professional bodies, provide additional layers of control inhibiting regional campuses from responding to local needs and conditions with adaptations that would enhance the richness of regional and rural student learning experiences. Bureaucratic inflexibility as described here sits in tension with current government policies aspiring to increase participation and retention rates for rural students. This paper outlines and critiques some of the ways in which quality controls in higher education serve to damage regional student learning through the imposition of inflexible curriculum design and contextually incongruent teaching standards. The paper theorizes how greater operational flexibility can be achieved whilst assuring the quality of rural learning experiences. While the importance of professional accreditation and other proxy measures for quality learning are not denied, it should be possible to adopt some context-sensitive measures whilst maintaining standards in regional education. For example, the types of assessment tasks, class engagement activities and regionally relevant case studies tailored to the smaller class sizes typical of regional and remote campuses could be embraced as an opportunity rather than viewed as a deviation from standard.